Promotion of green technology under different environmental policies - John C. Strandholm (Games, 2020)
In this paper, I develop a two-stage game of pollution abatement technology adoption in a Cournot oligopoly to investigate a firm's decision to adopt pollution abatement technology. In particular, I study the adoption incentives and welfare implications of popular environmental policies, namely emission fees and quotas. Tradeable permits result in identical outcomes to emission fees. Within each policy regime, the conditions for Nash equilibria are identified where both firms invest in the green technology, neither firm invests in the technology, or only one firm invests. The following extensions are also analyzed: asymmetric adoption costs, increase in the marginal cost of production from adoption, and a type-dependent fee where adoption reduces the emission fee. Social welfare under an emission fee is identical to that under a quota. However, when policy is (not) stringent, firms are more willing to adopt expensive technology under a fee (quota) than under a quota (fee, respectively).
Keywords: D43; L51; Q52; 330; environmental regulation; green technology; technology adoption